Nanoporous copper as the hydrogen transfer catalyst for reduction of imines with silane/alcohol as the hydrogen source - Mengyuan Li; Weina Guo; Liying Zhang; Bosen Yang; Zhiwen Li (Results in Chemistry)
The design and synthesis of sustainable nanocatalysts for novel and improved organic transformation are key tasks in organic chemistry. In this study, surface-oxidized nanoporous copper (np-Cu) was prepared using a dealloying method and oxygen desiccation treatment. This nanoporous catalyst promoted the reductive amination of aldehydes, generating a series of N-alkylated secondary amines in high yields. Importantly, recycling experiments demonstrated that the np-Cu could be recovered and reused five times without any significant loss of activity. The obtained results indicate that np-Cu, which represents a tunable and economical nanoporous material, has the potential to be widely applied in other hydrogen transfer reactions.